THE ACQUISITION OF ENGLISH SENTENCES BY CHILDREN OF FOUR AND FIVE YEARS OLD - Yulima Melsipa Lingga; Widiya Astuti Alam Sur (Universitas Lambung Mangkurat, 2019)
The objectives of this research were to find out types of English sentences acquired by boys and girls of four and five years old children. This research also aims to find the tendency of English acquisition between boys and girls. The sources or subjects of this research were 20 kindergarten students of K-2 David in TK Kristen Kalam Kudus Pematangsiantar, 11 boys and 9 girls. The research design is qualitative research design. The instrument of data collection used video recording to observe the subjects in real situation and naturally. The result reveals that, the types of English sentences acquired by boys and girls of four and five years old children are declarative, interrogative, imperative, and exclamatory sentences, which are boys acquired interrogative sentences much more in their conversation while girls acquired declarative sentences more than other types. Girls or females articulate better and acquire a more extensive vocabulary than males or boys. Keywords: language acquisition, children of four and five, types of sentences